Experimental research on resource utilization of iron tailings powder in backfilling engineering - Guo-Hua Yuan; Yun-Shi Yao; Pu-Gang Zhang; Wei-Guo Hao; Kun-Peng Huang; Jin-Li; Qing-Fang Shang (Scientific Reports)
Abstract The goaf formed by mining and other activities is prone to safety hazards. Preparing high-quality and low-cost solidified iron tailings powder (SITP) is an important way to ensure backfill quality and eliminate safety hazards. Using iron tailings powder near the goaf of in Shanxi, comparative experiments were conducted to evaluate the the flowability, stone rate, strength, and water stability of newly mixed SITP under different types and dosages of curing agent, and mixing methods. The results show that under the premise of keeping the fluidity constant, the strength of the ITP slurry increases with the increase of the curing agent content; At the same strength, the water consumption significantly affects the fluidity; When using 8%~16% different curing agent dosage, the expansion degree is 280 mm ~ 600 mm, the wet density is 1.9 g/cm3 ~ 2.1 g/cm3, the 28d strength after curing is 1.4 MPa ~ 3.7 MPa, and the stone rate is greater than 92%; The ITP slurry prepared by vibration mixing with a mixing time of 120 s and the amount of curing agent at 8% meets the engineering application requirements of 7d strength of 0.6 MPa and expansion of 250 mm. The research shows that the iron tailings powder slurry prepared by vibration mixing has high strength after solidification, and it is a new way of resource utilization of iron tailings powder with large consumption and good economy to be used for goaf backfilling.